Reduction Of An Economy’s Raw Material Dependence And The Human Capital Of A Country - Perepelkin, Viacheslav; Perepelkina, Elena (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper evaluates the raw material dependence of two export-oriented oil and gas extracting countries. We find evidence of presence of the Dutch disease in both countries and of the resource curse in Russia. Reduction of volumes of crude oil and natural gas production and exports, compensated by the growth of value added in other kinds of economic activity, suggests that Norway is gradually overcoming the Dutch disease by means of expanded reproduction of human capital. On the other hand, extraction of hydrocarbons may remain a driver of the Russian economic growth.